Riparian Lowlands in Clay Till Landscapes: Part I—Heterogeneity of Flow Paths and Water Balances. Issue 4 (23rd April 2020) - Petersen, R. J.; Prinds, C.; Iversen, B. V.; Engesgaard, P.; Jessen, S.; Kjaergaard, C.
Abstract: Riparian lowlands act as interfaces between the streams and upland areas. This study identified and quantified local flow paths in four transects of a 26 ha Danish riparian lowland in a glacial till landscape. The riparian lowland was fed by drain water from the upland agricultural drainage catchments. Precipitation, stream stage, and drainage discharge into the riparian lowland were measured continuously, while groundwater hydraulic heads were measured in piezometer pipes twice per month. A water balance model was developed to quantify water fluxes leaving the riparian lowland area via evapotranspiration, leakage to a deeper aquifer, and via groundwater flow, drain flow, and overland flow to the adjacent stream. Overland flow originating from the tile drains was the main flow path in all four transects, and also fluxes to the stream via groundwater or lowland tile drains were significant in some subareas. The presence of a secondary tile drainage network within parts of the riparian lowland reduced overland flow and increased interaction with the riparian lowland soils. Area‐normalized fluxes varied greatly between transects, largely reflecting variations in hydraulic loading rate (ratio of water input rate to the area of the receiving riparian lowland). This, combined with the significance of groundwater flow and riparian lowland tile drain flow in some of the investigated transects, revealed a heterogeneous distribution of flow paths within the small headwater lowland. The rate of overland flow was highly correlated to the hydraulic loading rate, which in turn was dominated by the drainage discharge rate at the hillslope boundary. Key Points: Overland flow, bypassing the riparian lowland, is produced when the hydraulic loading exceeds riparian lowland infiltration Magnitudes of overland flow are correlated with the ratio of catchment area to riparian lowland area Riparian lowland drains reduce overland flow and increase water residence times